Phytochemical baicalin potentially inhibits Bcl-2 and VEGF: an in silico approach - Sharma, Vikas; Gupta, Arti; Singh, Mohini; Singh, Anshul; Chaudhary, Anis Ahmad; Ahmed, Zakir Hassain; Khan, Salah-ud-din; Rustagi, Sarvesh; Kumar, Sanjay; Kumar, Sandeep (Frontiers in Bioinformatics, 2025)
BackgroundThe rising prevalence of cancer cells exhibits uncontrolled growth and invasive and aggressive properties, leading to metastasis, which poses a significant challenge for global health. Central to cancer development are proteins such as NF-kB, p53, VEGF, and BAX/Bcl-2, which play important roles in angiogenesis, cell apoptosis regulation, and tumor growth.MethodologyThis in silico study evaluates the activity of six different natural as well as novel therapeutic strategies against cancer. Using a computational approach, i.e., virtual screening, molecular docking, and molecular dynamics (MD) simulations, the binding affinities and interactions of selected phytochemicals with cancer-specific proteins were analyzed. Key criteria for selection included binding affinity, molecular stability, and pharmacokinetic and toxicological properties. Post-selection, dynamics of ligand–protein interactions were further examined through MD simulations conducted using Desmond-Maestro 2020-4 on a Linux-based HP Z2 workstation, providing an insight into the conformational changes in the stability of the inhibitor–protein complexes. This was complemented by ADMET predictions to assess pharmacokinetics and toxicological profiles.ResultsOur findings reveal that out of six phytochemicals, baicalin exhibited the most promising results, with docking scores of −9.2 kcal/mol and −9.0 kcal/mol against Bcl-2 and VEGF receptors, respectively. The MD simulation (100 ns) confirmed the stability of baicalin–protein interactions, supported by hydrophobic interactions and intermolecular hydrogen bonds. The RMSD and RMSF values of baicalin exhibit an acceptable global minimum (3.5–6 Å) for p53, VEGF, and BAX/Bcl-2.ConclusionThis study highlights the potential of baicalin, a phytochemical known for anti-cancerous, anti-apoptotic, and anti-proliferative properties, as a promising candidate for cancer treatment. Further exploration and validation of its inhibitory mechanisms could open a promising avenue for therapeutic approaches in oncology.